2017
DOI: 10.1016/j.cub.2017.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Visual Input to the Drosophila Central Complex by Developmentally and Functionally Distinct Neuronal Populations

Abstract: Summary The Drosophila central brain consists of stereotyped neural lineages, developmental-structural units of macrocircuitry formed by the sibling neurons of single progenitors called neuroblasts. We demonstrate that the lineage principle guides the connectivity and function of neurons providing input to the central complex, a collection of neuropil compartments important for visually-guided behaviors. One of these compartments is the ellipsoid body (EB), a structure formed largely by the axons of ring (R) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
329
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 147 publications
(355 citation statements)
references
References 53 publications
25
329
1
Order By: Relevance
“…Internally, however, the bulb differed in the organization of GABA immunolabeling. In many species the bulb was a uniform entity, in others it was subdivided into distinct areas (Figures d, b, d,g, and d) indicating distinct subtypes of TL/R neurons (Müller et al, ; Omoto et al, ). An internal organization into microglomeruli up to a size of small somata was found in most butterfly species.…”
Section: Discussionmentioning
confidence: 99%
“…Internally, however, the bulb differed in the organization of GABA immunolabeling. In many species the bulb was a uniform entity, in others it was subdivided into distinct areas (Figures d, b, d,g, and d) indicating distinct subtypes of TL/R neurons (Müller et al, ; Omoto et al, ). An internal organization into microglomeruli up to a size of small somata was found in most butterfly species.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, DNcad has been used to define discrete compartments in the neuropile of the central brain. In particular, the so called “structured neuropil”, including the central complex, mushroom body, or antennal lobe exhibits modular subdivisions that are revealed by DNcad, or other markers that primarily highlight synaptic density (Pereanu et al, 2010; Ito et al, 2014; Omoto et al, 2017). The simultaneous labeling of all medulla layers by global marking techniques, rather than specific genetic markers that can only visualize one type of neuron/layer at a time, will be useful for future studies relying on the anatomical mapping of individual neurons, or classes of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study we had shown that the neural circuit providing visual input to the central complex, the anterior visual pathway (AVP), is formed by three lineages, DALv2, DALcl1, and DALcl2 (Omoto et al, ). Larvally‐born (secondary) neurons of DALv2 are confined to the ellipsoid body (EB) and its input compartment, the bulb (BU; Larsen et al, ; Spindler & Hartenstein, ; Wong et al, ; Figure ).…”
Section: Introductionmentioning
confidence: 99%
“… Anterior visual pathway of the Drosophila brain. Schematic frontal view of brain hemisphere depicting the neuronal elements forming the anterior visual pathway, as described in Omoto et al (). Medullo‐tubercular (MeTu) neurons project via the anterior optic tract to the lateral and intermediate domain of the anterior optic tubercle; AOTU).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation